2008
DOI: 10.1063/1.3002419
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of magnetization reversal influenced by current in perpendicularly magnetized Co/Pt thin film

Abstract: We have investigated thermally activated magnetization reversal influenced by the current in a Co/Pt thin film with perpendicular magnetic anisotropy at room temperature by measuring the extraordinary Hall effect. The magnetization could reverse in a fixed magnetic field lower than the coercive field as increasing the current, which depends on the current-sweep rate. The characteristic current for zero net magnetization is small for a low current-sweep rate and a high fixed field. Magnetization reversal become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This observation was soon confirmed by several groups using different magnetic stacks and heavy metal substrates (Avci et al, 2012(Avci et al, , 2014bEmori et al, 2013;Pai et al, 2012;Yu et al, 2014b), as well as antiferromagnets (Fukami et al, 2016b;Oh et al, 2016;Wadley et al, 2016), magnetic insulators (Avci et al, 2017a;Li et al, 2016b), and topological insulators (Han et al, 2017;Mahendra et al, 2018;Wang et al, 2017b). Notably, earlier investigations of Pt/Co/Pt and Pt/Co also reported an effect of very small current densities on the low temperature coercivity of Co, albeit mainly attributed to Joule heating (Lin et al, 2006;Riss et al, 2010;Xie et al, 2008).…”
Section: E Magnetization Switchingmentioning
confidence: 75%
“…This observation was soon confirmed by several groups using different magnetic stacks and heavy metal substrates (Avci et al, 2012(Avci et al, , 2014bEmori et al, 2013;Pai et al, 2012;Yu et al, 2014b), as well as antiferromagnets (Fukami et al, 2016b;Oh et al, 2016;Wadley et al, 2016), magnetic insulators (Avci et al, 2017a;Li et al, 2016b), and topological insulators (Han et al, 2017;Mahendra et al, 2018;Wang et al, 2017b). Notably, earlier investigations of Pt/Co/Pt and Pt/Co also reported an effect of very small current densities on the low temperature coercivity of Co, albeit mainly attributed to Joule heating (Lin et al, 2006;Riss et al, 2010;Xie et al, 2008).…”
Section: E Magnetization Switchingmentioning
confidence: 75%
“…[3][4][5][6][7] Recent studies on materials with perpendicular anisotropy have revealed a higher efficiency for CIDM than in the case of in-plane magnetized materials. [8][9][10][11] Especially the contributions of the adiabatic 12,13 and nonadiabatic spin torque due to spin relaxation [14][15][16] or momentum transfer 12,14 to the domain wall ͑DW͒ motion and their dependence on the material properties are so far not fully understood. In particular, studies on Co/Pt multilayers show a large nonadiabaticity factor ␤.…”
mentioning
confidence: 99%
“…The latter includes the bulk spin Hall effect (SHE), [28][29][30][31] topological surface states, [32,33] interfacial SOC effects, [34][35][36][37][38] orbit-spin conversion, [39] the anomalous Hall effect, [40] the planar Hall effect, [41,42] the magnetic SHE, [41][42][43][44][45] Dresselhaus effect, [46] etc. The bulk SHE has been widely observed in thin-film heavy metal (HM), [4][5][6][7][8][9][10][11][12][47][48][49] Bi-Sb, [50] Bi x Te 1−x , [51] CoPt, [52] FePt, [53] Fe x Tb 1−x , [54] and Co-Ni-B. [55] Generation of transverse spins by the SHE can be highly efficient as indicated by the giant interfacial damping-like SOT efficiency of ≥0.25.…”
Section: Electrical Generation Of Spin Currentsmentioning
confidence: 99%
“…Since the discovery that an in-plane charge current in certain heavy metal thin films can be utilized to manipulate and excite the magnetization state of an adjacent ferromagnetic layer, [2][3][4][5][6][7][8][9] spin-orbit torques (SOTs) have become a powerful and versatile tool to manipulate magnetic materials. SOTs are exerted when angular momentum is transferred from a spin current or spin accumulation.…”
Section: Introductionmentioning
confidence: 99%